Working Paper 45: Strategic anti-corruption communications: Guidance for behaviour change interventions - Baez Camargo, Claudia; Schönberg, Johanna (Basel Institute on Governance Working Papers, 2023)
This Working Paper is intended to guide practitioners who are seeking to complement conventional anti-corruption measures by adopting a behavioural communications approach. It aims to connect a typology of anti-corruption messages with behavioural change theories, and discuss their impact. Subsequently, it suggests practical implications for designing anti-corruption communication as part of behaviour change interventions. This includes outlining how to develop a robust Theory of Change as a means to enhance the success of such efforts. The guidance is based on a review of seven key topically pertinent studies that have been recently published. This publication is prepared as guidance for the USAID Indonesia Integrity Initiative (USAID INTEGRITAS).